2018
DOI: 10.1186/s12887-018-1068-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of low birth weight and its co-variants in Bangladesh based on a sub-sample from nationally representative survey

Abstract: BackgroundLow birth weight (LBW) remains a leading global cause of childhood morbidity and mortality. This study leverages a large national survey to determine current prevalence and socioeconomic, demographic and heath related factors associated with LBW in Bangladesh.MethodsData from the Multiple Indicator Cluster Survey (MICS) 2012–13 of Bangladesh were analyzed. A total of 2319 women for whom contemporaneous birth weight data was available and who had a live birth in the two years preceding the survey were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 23 publications
16
80
2
Order By: Relevance
“…The prevalence of low birth weight in our study using mother’s perception about baby’s size at birth was about 20%. According to the National Low Birth Weight Survey Bangladesh 2015, the prevalence of low birth weight using the WHO cut-off of <2500 grams was 22% [4,10]. Similar prevalence estimates using these two different methods for defining low birth weight have increased reliability of our findings.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The prevalence of low birth weight in our study using mother’s perception about baby’s size at birth was about 20%. According to the National Low Birth Weight Survey Bangladesh 2015, the prevalence of low birth weight using the WHO cut-off of <2500 grams was 22% [4,10]. Similar prevalence estimates using these two different methods for defining low birth weight have increased reliability of our findings.…”
Section: Discussionsupporting
confidence: 65%
“…There is a large disparity in the burden of low birth weight in the developed and developing countries. Also, south Asian countries harbour a large number of low birth weight babies due to higher birth rate as well as higher prevalence rate of low birth weight [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal growth restriction is a major public health problem worldwide (Black et al, ) and particularly in Bangladesh (Christian et al, ; Islam et al, ; Khan, Islam, Awan, & Muurlink, ; Klemm et al, ; Mridha et al, ). Newborn anthropometric outcomes such as low birthweight (LBW), stunting at birth, and small for gestational age (SGA) are highly prevalent in low‐ and middle‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Newborn anthropometric outcomes such as low birthweight (LBW), stunting at birth, and small for gestational age (SGA) are highly prevalent in low-and middle-income countries. In Bangladesh, the prevalence of LBW in 2012-2013 was 20% (Khan et al, 2018), prevalence of newborn stunting in various studies is of similar magnitude Klemm et al, 2015 ;Mridha et al, 2016), and SGA is very common (e.g., 67.3% of infants born to mothers who received iron and folic acid during pregnancy, as stated in Klemm et al, 2015;Mridha et al, 2016). Birth length has been shown to be associated with compromised cognitive development (Lee et al, 2018), and LBW and restricted intrauterine growth have been linked with other longer term outcomes such as attained height, achieved schooling/education, and income later in life (Victora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A research conducted in different countries on determinants of LBW showed that various sociodemographic, socioeconomic, pregnancy and maternal health service-related and communityrelated factors to be predictors of low birth weight (18,21,22). In Ethiopia, prior studies have been done to identify sociodemographic, pregnancy, and maternal health service-related factors (20)(21)(22)(23). Even though the low birth weight was affected by factors operating at both individual and community level none of the studies have tried to look at the factors that affect LBW at community and individual levels simultaneously.…”
mentioning
confidence: 99%